China and Japan in Africa: the case of FOCAC and TIDAL - Monyae, Lennon (My University, 2017)
This dissertation investigates FOCAC and TICAD contributions towards development on the African continent. The research explains the architecture of the latter conference diplomacy institutions. Japan and China are argued to be competing through evidence from the different fields that give foreign assistance to. Jospeh Nye’s soft power as theoretical framework will guide the research’s understanding of Chinese and Japanese engagements in African development. The research found that FOCAC outweighed TICAD in financial contributions however TICAD through JICA had more grassroots level contributions. China was seen to be focused on bilateral relations aimed at supporting state-led companies in big infrastructure development. Japan is argued to be more engaging with external actors while supporting African development and in addition, showed more support for the African Union’s policies. China has ‘win-win’ and Japan has ‘partnership’ both in line with African Pan -African ideals. Africans are lacking policy and guidelines in dealing with foreign partners and argued to organise themselves and respond to Japanese and Chinese interests collectively. Agenda 2063 that mentions external partners as a source of funding for development is not enough to use a policy. African development policies are seen to have failed previously due to unfulfilled promises from external partners. The research argues that African people should take FOCAC and TICAD as learning spaces and take a leadership role in their own development.
Research report submitted towards the award of Master of Arts Department of International Relations University of the Witwatersrand, Johannesburg, 2017
Keywords: Economic development--Africa; Investments, Foreign--Africa; China--Foreign economic relations--Africa; Africa--Foreign economic relations--China; Japan--Foreign economic relations--Africa; Africa--Foreign economic relations--Japan; Africa--Economic conditions